2015
DOI: 10.1128/jvi.03337-14
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Toll-Like Receptor 4 (TLR4) and TLR7 Ligands as Influenza Virus Vaccine Adjuvants Induce Rapid, Sustained, and Broadly Protective Responses

Abstract: Current vaccines against influenza virus infection rely on the induction of neutralizing antibodies targeting the globular head of the viral hemagglutinin (HA). Protection against seasonal antigenic drift or sporadic pandemic outbreaks requires further vaccine development to induce cross-protective humoral responses, potentially to the more conserved HA stalk region. Here, we present a novel viral vaccine adjuvant comprised of two synthetic ligands for Toll-like receptor 4 (TLR4) and TLR7. 1Z105 is a substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 59 publications
6
106
2
1
Order By: Relevance
“…The enhanced clearance of bacteria following B. pertussis challenge of mice immunized with aP+alum-TLR7a is likely to be mediated by a combination of different immune responses, including cytokine secretion by Th1 and Th17 cells, leading to enhanced recruitment and activation of phagocytic cells, and higher titres of IgG2a/b antibodies titres, that are known to promote opsonization and complement-mediated killing of bacterial cells. Similar to our findings, addition of a TLR7 agonist to an influenza vaccine formulation promoted protective IFN-c and IgG2a responses in mice [20]. Importantly, TLR7-adjuvanted influenza vaccine produced potent immune responses with low reactogenicity.…”
Section: Discussionsupporting
confidence: 76%
“…The enhanced clearance of bacteria following B. pertussis challenge of mice immunized with aP+alum-TLR7a is likely to be mediated by a combination of different immune responses, including cytokine secretion by Th1 and Th17 cells, leading to enhanced recruitment and activation of phagocytic cells, and higher titres of IgG2a/b antibodies titres, that are known to promote opsonization and complement-mediated killing of bacterial cells. Similar to our findings, addition of a TLR7 agonist to an influenza vaccine formulation promoted protective IFN-c and IgG2a responses in mice [20]. Importantly, TLR7-adjuvanted influenza vaccine produced potent immune responses with low reactogenicity.…”
Section: Discussionsupporting
confidence: 76%
“…A striking result to emerge from this study was that specific combinations of TLR ligands induced a greatly enhanced antibody response and long-lived germinal center (GC) responses similar to those observed in live viral infections (14). The observation that specific combinations of TLR ligands enhance antibody responses has been confirmed by recent studies (15)(16)(17).…”
supporting
confidence: 64%
“…Animals were bled ϳ4 weeks before primary immunization for baseline analysis of serological and cellular immune responses. Animals were immunized 4 times at weeks 0, 8,16, and 25. Animals were rested for 4 months and subjected to a series of challenges with 20,000 TCID 50 (0.5 to 1.0 AID 50 ) every week for 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Agonists of nucleic acid recognition pathways are promising novel candidates that license DCs for the induction of protective immune responses mediated by both T H 1 cells and cytotoxic CD8 + T cells 59 . The combined use of different agonists may prove even more powerful, as recent data have indicated that co-engagement of multiple nucleic acid receptors elicited the most potent immune responses in preclinical trials of vaccine adjuvants 60,61 .…”
Section: Biomarkersmentioning
confidence: 98%